A Novel Nonsense Mutation of POU4F3 Gene Causes Autosomal Dominant Hearing Loss - Chi Zhang; Mingming Wang; Yun Xiao; Fengguo Zhang; Yicui Zhou; Jianfeng Li; Qingyin Zheng; Xiaohui Bai; Haibo Wang (Neural Plasticity)
POU4F3 gene encodes a transcription factor which plays an essential role in the maturation and maintenance of hair cells in cochlea and vestibular system. Several mutations of POU4F3 have been reported to cause autosomal dominant nonsyndromic hearing loss in recent years. In this study, we describe a pathogenic nonsense mutation located in POU4F3 in a four-generation Chinese family. Target region capture sequencing was performed to search for the candidate mutations from 81 genes related to nonsyndromic hearing loss in this family. A novel nonsense mutation of POU4F3, c.337C>T (p. Gln113⁎), was identified in a Chinese family characterized by late-onset progressive nonsyndromic hearing loss. The novel mutation cosegregated with hearing loss in this family and was absent in 200 ethnicity-matched controls. The mutation led to a stop codon and thus a truncated protein with no functional domains remained. Transient transfection and immunofluorescence assay revealed that the subcellular localization of the truncated protein differed markedly from normal protein, which could be the underlying reason for complete loss of its normal function. Here, we report the first nonsense mutation of POU4F3 associated with progressive hearing loss and explored the possible underlying mechanism. Routine examination of POU4F3 is necessary for the genetic diagnosis of hereditary hearing loss in the future.